Association of hematological parameters and inflammatory indices with sarcopenia in the United States and China: a cross-sectional study - Ying Cheng; Chen Kuang; Gang Zhang; Zhongzheng Zhang; Kunpeng Qin (European Journal of Medical Research)
Abstract Background In this study, we examined the association between hematological parameters and inflammatory indices and sarcopenia in the general population of the United States and China. Methods The cross-sectional study was conducted using data from the National Health and Nutrition Examination Survey (NHANES) (2011–2014) and the Affiliated Hospital of Anhui Medical University (2022–2024). We employed weighted restricted cubic spline (RCS) plots and multivariable logistic regression analyses to explore the association of hematological parameters and inflammatory indices with the prevalence of sarcopenia in American and Chinese populations. Results A total of 8805 participants from NHANES, and 2598 individuals from the First Affiliated Hospital of Anhui Medical University were included in our analysis. In American and Chinese populations, the roughly J-shaped curve was detected in the RCS plots for mean platelet volume and platelet-to-lymphocyte ratio with the risk of sarcopenia. Additionally, the risk of sarcopenia was positively and linearly associated with white blood cells, lymphocytes and platelet, while it was inversely and linearly associated with mean cell volume. Conclusions We demonstrated a nonlinear association between some hematological parameters, inflammatory indices and sarcopenia in American and Chinese populations. The need to focus more on hematological parameters and inflammatory indices in the body could provide better prevention strategies for sarcopenia.